Isolated and combined effects of EVA and TPU custom foot orthoses on constant speed, treadmill running kinematics - Van Alsenoy, Ken; van der Linden, Marietta L.; Ryu, Joong Hyun; Girard, Olivier; Al Raisi, Lubna; Santos, Derek (Frontiers in Earth Science, 2023)
Introduction: We investigated the isolated and combined (HYB) effects of ethylene-vinyl acetate (EVA) and expanded thermoplastic polyurethane (TPU) custom foot orthoses (CFOs), compared to a control condition (CON; shoes only), on constant speed, treadmill running kinematics. Methods: Twenty (10 male and 10 female subjects) well-trained runners performed four 6-min bouts at the same individualized speed for each bout on a treadmill under four footwear conditions (EVA, TPU, HYB, and CON). Twenty markers and four clusters (four markers each) were placed on lower limbs and the pelvis. Lower limb and pelvis movements were tracked using a three-dimensional motion capture system with 11 cameras (Vicon MX System, Oxford, United Kingdom). Lower limb joint angles and angular velocity were normalized to 100% of the stance phase. Results: Peak ankle eversion (p < 0.001, η2 = 0.72), peak ankle eversion angular velocity (AV) (p < 0.001, η2 = 0.64), peak ankle inversion AV (p < 0.001, η2 = 0.60), and peak ankle internal rotation AV (p < 0.001, η2 = 0.49) demonstrated the largest differences between conditions. Statistical non-parametric mapping analysis revealed that HYB exhibited the largest proportions of change during the total stance phase compared to the CON. Discussion: All CFO materials caused significant reductions in peak angles and peak AVs at the ankle in the frontal plane, with more pronounced effects for harder (EVA) than softer (TPU) materials. These significant reductions occurred during large portions of the total stance phase for the angles and for the AVs. Although some effects could be found in more proximal joints such as the knee and hip, most significant effects were found at the ankle joint. Overall, combining hard EVA material in the heel and soft TPU in the forefoot (HYB) resulted in significant, more favorable changes compared to the CON that lasted for the largest proportion of stance phase when compared to wearing shoes only.